A review of gold extraction using alternatives to cyanide: Focus on current status and future prospects of the novel eco-friendly synthetic gold lixiviants. (January 2022) - Zhang, Yan; Cui, Mingyao; Wang, Jianguo; Liu, Xiaoliang; Lyu, Xianjun
Highlights: Gold extraction by novel eco-friendly synthetic gold lixiviants (NESGLs) was reviewed. Leaching efficacy, synthesis and properties of NESGLs were summarized and discussed. NESGLs have achieved some industrial application due to a series of advantages. Future research efforts for promoting the application of NESGLs were suggested. Abstract: Cyanide is currently the predominant lixiviant for gold extraction. However, cyanide is highly toxic, causing potential environmental hazards and high detoxification costs. This has initiated extensive research aimed at seeking and developing eco-friendly substitutes for cyanide. Although significant research has been undertaken, most, if not all, of the traditional non-cyanide lixiviants such as thiosulfate, thiourea, halide and thiocyanate have proven to be difficult to achieve widespread adoption at gold mines because of their inherent limitations. In recent years, a range of novel eco-friendly synthetic gold lixiviants (NESGLs) such as "Jinchan", one of the most representative products, have been developed successfully. Compared with cyanide, these NESGLs are much less or non-toxic, and have achieved comparable gold recoveries from ores without changing the original cyanidation process and equipment. The successful development of NESGLs appears to be making significant inroads into the dominance of cyanide, as evidenced by a growing number of their industrial applications at gold mines worldwide. This paper reviews the current status of gold extraction from its ores using the NESGLs with details focused on their leaching efficacy, synthesis, and composition as well as possible leaching mechanisms. Their future perspectives and developing trends of considerable concern are also discussed.